1992
DOI: 10.1002/ddr.430260402
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin mechanisms in the central nervous system: A target for drug development

Abstract: Endothelin (ET), a vasoconstrictor peptide, was isolated and characterized in 1988. Since then extensive studies have been done in different animal species to identify its receptors in central nervous system (CNS) and peripheral tissues. Three forms of ETs have been identified: ET‐1, ET‐2, and ET‐3. Their distribution pattern and pharmacological functions have been defined. ET‐1 and ET‐2 are mainly distributed in the CNS, including spinal cord and the peripheral tissues, while ET‐3 although present in other ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 195 publications
1
14
0
Order By: Relevance
“…The role of ET in the regulation and secre tion of several endocrine hormones is being increasingly implicated [23], The present study provides further evidence in support of studies conducted earlier indicating that ET mechanisms are involved in the thyroid dysfunction. Studies conducted earlier had shown that ET receptors are down-regulated in the pituitary, and plasma ET-1 concentra tion was increased in hyperthyroid rats [20], The present study showed that the concentra-…”
Section: Discussionsupporting
confidence: 80%
“…The role of ET in the regulation and secre tion of several endocrine hormones is being increasingly implicated [23], The present study provides further evidence in support of studies conducted earlier indicating that ET mechanisms are involved in the thyroid dysfunction. Studies conducted earlier had shown that ET receptors are down-regulated in the pituitary, and plasma ET-1 concentra tion was increased in hyperthyroid rats [20], The present study showed that the concentra-…”
Section: Discussionsupporting
confidence: 80%
“…ET binding sites have been identified in the heart [2], blood vessels and central nervous system (CNS) [1,3]. The ma jor biological action of ET is vasoconstriction [4], However, in addition, ET has several important cardiovascular, renal and endo crine functions [1,5], Studies indicate that both central and peripheral ET mechanisms are involved in blood pressure regulation. Intracerebroventricular injection of ET in con scious normotensive Wistar-Kyoto (WKY) rats increased blood pressure in a dose-related manner [6].…”
Section: Introductionmentioning
confidence: 99%
“…Widely distributed throughout many tis sues, endothelin (ET) exerts its biological ac tions by acting on specific receptors on cell membranes [1]. ET binding sites have been identified in the heart [2], blood vessels and central nervous system (CNS) [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms involved in tolerance after chronic administration of opiates are extremely complex, involving changes in opiate signal transduction and interactions between opiate and non-opiate systems [9]. The ET system in the central nervous system (CNS) has been shown to be a potent regulatory system for the sympathetic nervous system [27,31]. ET antagonists have also been shown to block sympathetic nervous systemmediated responses of clonidine and propranolol [32,33].…”
Section: Discussionmentioning
confidence: 99%